ANALISIS PENGHEMATAN BIAYA PENGGUNAAN BEKISTING PELAT LANTAI KONVENSIONAL MODEL PANEL PADA BANGUNAN TIPIKAL (STUDI KASUS PADA PROYEK AMARTHA RESIDENCE) - I Made Pandu Weda Wiguna; I Gusti Agung Adnyana Putera; G.A.P Candra Dharmayanti (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2018)
Formwork planning requires a consideration of the use of method or system to make it more efficient and economical, especially for a typical building. That is the building that has the same shape and size as each other. Work of formwork slabs is one of the types of jobs that produce residual waste material. Floor slab formwork can generally be used one time only compared with column formwork that can be used repeatedly in a building. In general,material of floor slab formwork of conventional model panel is almost the same as the floor slab formwork, i.e. they are still using wood, multiplex, and spikes so the cost is still affordable. The difference is only related to the shape that is adjusted with the size of the multiplex and the floor slab of the building. This will minimizewasted multiplex, make installation easier and reduce the damage at the time of demolition.This study aimed to review the cost savings resulting from the use of formwork with panel model of floor slab, with the case study on Amartha Residence Development Project. This project had several types of residences, one of them wasSoho Verdetype, with an area of ??145/105 m2and consisted of 20 units. This research used quantitative descriptive analysis, by calculating the needs of the conventional panel model formwork slabs based on the existing volume. The analysis showed that the panel method could be used as much as 6 times, whichsavethe cost of Rp. 455,983,209.32 (69%) from the initial cost plan of the formwork slabs for 20 units of the buildings (Rp. 657,273,094.52). Keywords: Cost efficiency, Use of Formwork, Methods of Implementation